Pengaruh Kompensasi dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan pada PT Eka Mas Republik Cabang Depok - Marshella Dwi Restu; Ade Sri Mulyani (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
Job satisfaction is a response given by employees to their work, both in the form of positive responses and negative responses. Compensation and work motivation have an important role in influencing employee job satisfaction. The main objective of this research is to explore and analyze the relationship between compensation variables (X1), work motivation (X2), and employee job satisfaction (Y). The research method used is quantitative statistics. By using a questionnaire as the main instrument for data collection. The respondents involved in this research were 81 AE (Account Executives) at PT. Eka Mas Republik Depok branch. Data processing uses the SPSS 20 application with data analysis techniques using multiple linear regression to test the research hypothesis. The research results show that compensation (X1) and work motivation (X2) partially and simultaneously have a significant effect on employee job satisfaction Eka Mas Republik Depok branch.